A comprehensive map of preferentially located motifs reveals distinct proximal cis-regulatory sequences in plants - Rozière, Julien; Guichard, Cécile; Brunaud, Véronique; Martin, Marie-Laure; Coursol, Sylvie (Frontiers in Plant Science, 2022)
Identification of cis-regulatory sequences controlling gene expression is an arduous challenge that is being actively explored to discover key genetic factors responsible for traits of agronomic interest. Here, we used a genome-wide de novo approach to investigate preferentially located motifs (PLMs) in the proximal cis-regulatory landscape of Arabidopsis thaliana and Zea mays. We report three groups of PLMs in both the 5’- and 3’-gene-proximal regions and emphasize conserved PLMs in both species, particularly in the 3’-gene-proximal region. Comparison with resources from transcription factor and microRNA binding sites shows that 79% of the identified PLMs are unassigned, although some are supported by MNase-defined cistrome occupancy analysis. Enrichment analyses further reveal that unassigned PLMs provide functional predictions that differ from those derived from transcription factor and microRNA binding sites. Our study provides a comprehensive map of PLMs and demonstrates their potential utility for future characterization of orphan genes in plants.